Cross-Cultural Perspectives on Financial Inclusion and Sustainable Economic Growth: A Comparative Study between Brunei Darussalam, Eritrea, and Nicaragua - Siti Noor Hidaya; Samuel Tesfaye; Esmeralda Ruiz (Journal GoodWill, 2024)
This study investigates the cross-cultural dimensions of financial inclusion and its relationship with sustainable economic growth in Brunei Darussalam, Eritrea, and Nicaragua—three countries with distinct institutional and socio-cultural frameworks. Employing a mixed-methods comparative approach, the research integrates panel data analysis (2013–2023) with qualitative insights from 90 policymakers, financial practitioners, and micro-entrepreneurs. Quantitative results derived from the World Bank Global Findex, IMF Financial Access Survey, and UNDP Human Development Reports indicate a significant positive relationship between financial inclusion and sustainable growth, although the magnitude of this effect varies by country. Brunei exhibits the highest inclusion index due to strong digital infrastructure and supportive regulatory systems. Eritrea demonstrates limited progress constrained by weak institutional capacity, while Nicaragua shows moderate growth through community-based microfinance initiatives. Qualitative thematic analysis highlights three mediating factors—cultural trust, institutional readiness, and digital adoption—that shape inclusive financial ecosystems. The findings emphasize that financial inclusion is not merely an economic instrument but a culturally embedded process influenced by governance, social capital, and policy innovation. This study contributes to comparative financial development literature by revealing how cultural and institutional diversity conditions the inclusivity–growth nexus. Policy implications include the need for culturally adaptive strategies, enhanced digital infrastructure, and capacity building in local institutions to promote equitable and sustainable economic outcomes across developing regions.